Forms of subjectification - Matteo Finco (Oñati Socio-Legal Series)
Health represents a context where it is possible to observe the relationship between individuals and society, namely which spaces of autonomy are left for the individuals and which social forces are exercised on them. If Critical Theory points out the mechanisms of a neoliberal matrix that makes individuals “subjugate subjects”, Social System Theory allows to investigate how they are “included” in various spheres of society. Integrating these theories, we investigate mechanisms of subjectification on health. Moreover, through the analysis of the recent Italian law on advance directives and living will, we question if the claims of self-determination expressed by individuals could represent a form of “resistance” against neoliberal policies. Through a theoretical reflection and an analysis of the background and the juridical consequences of the law n. 219/2017, we conclude that the individual autonomy could be exercised together with responsibility towards others, balancing individual needs and claims with social solidarity.